1998
DOI: 10.2337/diacare.21.9.1495
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Function Test of Vasoconstrictor Changes in Foot Arteries in Diabetic Patients

Abstract: We conclude that the %RI of the digital artery is a useful and reliable sympathetic function test of early phase in diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
1
7
1
Order By: Relevance
“…These studies have confirmed the hypothesis of a hyperperfusion state in the lower extremities at an arteriovenous shunt volume that was increased up to threefold due to opening of the sympathetically controlled resistance vessels (7,10). Furthermore, other workers reported a reduction in the response to sympathetic stimulation (10,11). In ϳ50% of a cohort of diabetic patients, an abnormal skin blood flow has been observed at the index finger and a nondiscernible decrease or abnormal latencies after stimulation was reported (9).…”
supporting
confidence: 67%
See 1 more Smart Citation
“…These studies have confirmed the hypothesis of a hyperperfusion state in the lower extremities at an arteriovenous shunt volume that was increased up to threefold due to opening of the sympathetically controlled resistance vessels (7,10). Furthermore, other workers reported a reduction in the response to sympathetic stimulation (10,11). In ϳ50% of a cohort of diabetic patients, an abnormal skin blood flow has been observed at the index finger and a nondiscernible decrease or abnormal latencies after stimulation was reported (9).…”
supporting
confidence: 67%
“…This technique can be applied under conditions at rest and during sympathetic stimulation by means of a deep inspiratory gasp (10) or an electric stimulus (9). Alternatively, venous plethysmography (6) and duplex Doppler sonography (11) have been used. These studies have confirmed the hypothesis of a hyperperfusion state in the lower extremities at an arteriovenous shunt volume that was increased up to threefold due to opening of the sympathetically controlled resistance vessels (7,10).…”
mentioning
confidence: 99%
“…First, the autonomic denervation is believed to develop MAC (30) and could be biologically linked to arterial wall stiffness. Second, however, sympathetic failure affects microvascular blood flow by continuously opening arteriovenous shunts and increasing flow volume (31). It may be important that a concomitant abnormality, such as basement membrane thickness, regulates vascular resistance to blood flow, although there was no explanation for microangiopathy as a determinant factor of flow volume in the present study (32).…”
Section: Clinical Characteristics In All Subjectscontrasting
confidence: 49%
“…Little is known about the length dependence of the effects of diabetes on autonomic neurons. However, because deficits in sympathetic nerve-mediated vasoconstriction of arteries supplying skin of the hands and feet can be an early sign of diabetic autonomic neuropathy (13,35), sympathetic neurons with long axons may also be particularly susceptible to the effects of diabetes. In rat tail artery, STZinduced diabetes is reported to produce a length-dependent increase in the neuronal content of biogenic amines (norepinephine, adrenaline, serotonin, and dopamine), with the most marked changes occurring in the most distal region of this vessel (20).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have demonstrated that both type 1 (insulin dependent) and type 2 (noninsulin dependent) diabetic patients with signs of sensory and/or autonomic neuropathy (e.g., orthostatic hypertension) have increased skin blood flow under basal conditions (2,33) and attenuated reductions in skin blood flow (i.e., vasoconstriction) in response to sympathetic arousal [e.g., produced by mental arithmetic (2) or postural stimuli (29)]. Importantly, deficits in sympathetic vasoconstriction of arterial vessels supplying plantar skin can be demonstrated in both type 1 and type 2 diabetic patients at an early phase of diabetic neuropathy (31,35), perhaps suggesting that sympathetic neurons supplying these vessels are particularly vulnerable to the effects of diabetes. Furthermore, it has been suggested that reduced sympathetic nerve-mediated vasoconstriction of these vessels is an early change that contributes to the etiology of microangiopathy in skin of the feet (7).…”
mentioning
confidence: 99%